2022
DOI: 10.1002/nop2.1452
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' experiences of person‐centred care planning using video‐conferencing

Abstract: Frail older persons are recognized as an especially vulnerable patient group. They are dependent on coordinated and integrated healthcare efforts, provided by healthcare professionals from hospitals, primary care and municipal care. The increasing number of older persons with complex illnesses, and shorter inpatient care, calls for provision of care closer to home and emphasizes the need for collaboration between healthcare providers (Dahl et al., 2014), especially in connection with discharge from inpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Studies have shown that nurses perceive that digital tools make their work more efficient and that patients become more involved in their care (Huter et al , 2020; Schoultz et al , 2022), so they are often positive about the use of digital tools. However, it is also apparent that interactions between the healthcare professionals and patients become challenging when communicating via digital tools (Hedqvist et al , 2022). Moreover, new digital tools initially contribute to increased work intensity (Gough et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that nurses perceive that digital tools make their work more efficient and that patients become more involved in their care (Huter et al , 2020; Schoultz et al , 2022), so they are often positive about the use of digital tools. However, it is also apparent that interactions between the healthcare professionals and patients become challenging when communicating via digital tools (Hedqvist et al , 2022). Moreover, new digital tools initially contribute to increased work intensity (Gough et al , 2014).…”
Section: Introductionmentioning
confidence: 99%